Whole-Cell Microbial Bioreporter for Soil Contaminants Detection - Zeng, Ni; Wu, Yichao; Chen, Wenli; Huang, Qiaoyun; Cai, Peng (Frontiers in Bioengineering and Biotechnology, 2021)
Anthropogenic activities have released various contaminants into soil which pose a serious threat to the ecosystem and human well-being. Compared to conventional analytical methodologies, microbial cell-based bioreporters are offering a flexible, rapid and cost-effective strategy to assess the environmental risks. This review aims to summarize the recent progress in the application of bioreporters in soil contamination detection and provide insight into the challenges and current strategies. The biosensing principles and genetic circuit engineering are introduced. Developments of bioreporters to detect and quantify heavy metal and organic contaminants in soil are reviewed. Moreover, future opportunities of whole-cell bioreporters for soil contamination monitoring are discussed.